Pengaruh Penerapan Ice Breaking Terhadap Motivasi Belajar Pendidikan Agama Kristen Dan Budi Pekerti Kelas VII SMP Negeri 1 Sitio Tio Kabupaten Samosir Tahun Pelajaran 2023/2024 - Pevrina Sitanggang; Simion D. Harianja; Oktober Tua Aritonang; Risden Anakampun; Robinhot Sihombing (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
The purpose of this research is to determine the effect of implementing Ice Breaking on the learning motivation of Christian Religious Education and Character Education for class VII students at SMP Negeri 1 Sitio Tio, Samosir Regency, Academic Year 2023/2024. The method in this research is a pre-experimental design research method in the form of "One Shot Case Study". The population is all class VII students of SMP Negeri 1 Sitio-tio Samosir Regency for the 2023/2024 academic year, totaling 105 people and a sample of 35 people was determined using a purposive sampling technique. Data was collected using a positive closed questionnaire with 31 items, namely 15 items for variable Samosir Regency for the 2023/2024 Academic Year is known based on: 1) Analysis requirements test: a) positive relationship test obtained by the value rxy = 0.580 > rtable(=0.05,n=35) = 0.334. b) Testing a significant relationship obtained tcount= 4.090 > ttable(=0.05, dk=n-2=33)= 2.042. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂="36.05"+0.71X. b) Regression coefficient of determination test (r2) = 33.6%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=15, dk denominator=n-2=35-2=33) namely 16.70 > 2.01. Thus Ha is accepted and H0 is rejected.